Factors Associated With Functional Recovery Among Older Survivors of Major Surgery - Becher, Robert D. (Ann Surg, 2020)
OBJECTIVE: The objectives of the current study were 2-fold: first, to evaluate the incidence and time to recovery of premorbid function within 6 months of major surgery and second, to identify factors associated with functional recovery among older persons who survive a major surgery with increased disability. BACKGROUND: Most older persons would not choose a surgical treatment resulting in persistently increased postsurgical disability, even if survival was assured. Potential predictors of functional recovery after major surgery have, however, not been well-studied among geriatric patients. METHODS: It is a prospective longitudinal study of 754 community-living persons 70 years or older. The analytic sample included 266 person-admissions in which participants survived major surgery with increased disability and were monitored on a monthly basis for 6 months. RESULTS: Of the 266 person-admissions assessed, 174 (65.4%) recovered to their presurgical level of function, with median time to recovery of 2 months (interquartile range, 1–3), whereas 16 (6.0%) died. Two factors were significantly associated with an increased likelihood of functional recovery: being nonfrail (hazard ratio 1.60; 95% confidence interval 1.03–2.51; P = 0.038) and having elective surgery (hazard ratio 1.72; 95% confidence interval 1.14–2.59; P = 0.009). Three factors were associated with a reduced likelihood of functional recovery: hearing impairment, greater increase in postsurgical disability in the month after hospital discharge, and years of education. CONCLUSIONS: Among older persons, nonfrailty and elective surgery were positively associated with functional recovery, whereas hearing impairment, greater increases in postsurgical disability, and years of education were associated with higher risk of protracted disability.